Halaqoh Tentang Tata Cara Memakai Mukena Dalam Sholat Beserta Hukum Memakai Mukena Potongan dan Motif Pada Anak-Anak Di TPQ Miftahul Huda 2 Kampung Baru - Atik Vikhoirotin (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2023)
The command to close the genitals comes from Allah SWT who has made humans, while humans only receive everything that is given by Allah such as eating, drinking, health, sustenance and the like. Islam has outlined the limits of genitalia for men and women. The basic awrah for men is to cover between the navel and the knees, while the awrah for women is to cover the whole body except the face and palms. All Imam Madzhab require covering the genitals so that one's prayer becomes valid, but the fuqoha differ in setting the limits of genitalia for men, women and female servants.Just like the provisions on covering women’s how to wear genitals in prayer and the how to wear a mukena in prayer there are certainprovisions that must be observed such as the forehead must be visible, wrists are closed and the chin must be covered so that the prayer becomes valid, and the motives in wich have their own legal provisions to maintain prudence in the validity of the prayers performed.